CORE-PL Model and Student Independence: A Quantitative Study on Fiqh Learning Outcomes and Motivation in Secondary Schools - Falah, Syamsul; Hadjar, Ibnu; Sobirin, Moh.; Idaini, Moh. Wifaqul (Pascasarjana Universitas KH. Abdul Chalim, 2025)
In the realm of Islamic education, increasing motivation and learning outcomes in Jurisprudence requires the application of innovative learning models that suit the characteristics of the material and student needs. This research aims to examine the influence of the CORE-PL (Connecting, Organizing, Reflecting, Extending - Project Learning) learning model on motivation and learning outcomes in Jurisprudence, as well as identifying its influence with learning independence as a control variable. This research uses a quasi-experimental design carried out at MAN 1 Tegal. The sampling technique was carried out through random assignment involving 69 class XI students, divided into experimental and control classes. Data was collected through tests (learning outcomes), questionnaires (learning motivation and learning independence), and analyzed using simple Analysis of Variance (ANOVA) and Analysis of Covariance (ANCOVA). The research results show that the CORE-PL model has a significant influence on increasing student motivation and learning outcomes. In addition, when learning independence is used as a control variable, the influence of the CORE-PL model becomes stronger, which has implications for a significant increase in motivation and learning outcomes in Jurisprudence. This study contributes to the development of relevant active learning methods in the field of Jurisprudence education, and emphasizes the importance of student learning independence in supporting the effectiveness of the CORE-PL model. This conclusion confirms that the use of the CORE-PL learning model can be an effective solution for improving the quality of the learning process and Fiqh learning outcomes in madrasah.